Phase I/II study of adjuvant immunotherapy with sentinel lymph node T lymphocytes in patients with colorectal cancer - Zhen, Yun-Huan (Cancer Immunol Immunother, 2015)
Although the development of multi-disciplinary management has improved the survival of colorectal cancer (CRC), the prognosis of metastatic CRC patients remains poor. Accumulating evidence has demonstrated that immunotherapy with cancer vaccines and adoptive T cell transfusions may improve outcomes as an adjuvant to current standard CRC treatment. In this phase I/II study, 71 CRC patients who underwent radical surgery (stage I–III, n = 46) or palliative surgery (stage IV with non-resectable synchronous metastases, n = 25) were included. In the first part of this study, sentinel lymph nodes (SLNs) were intraoperatively identified in 55 patients (46 with stage I–III CRC and 9 with stage IV CRC). SLN-T lymphocytes were expanded ex vivo for a median of 28.5 days (range 23–33 days). Thereafter, a median of 153 × 10(6) cells (range 20.7–639.0 × 10(6)) were transfused. No treatment-related toxicity was observed. In the second part of this study, the stage IV patients were routinely followed. The 24-month survival rate of the SLN-T lymphocyte group was significantly higher than that of the control group: 55.6 versus 17.5 % (p = 0.02). The median overall survival of the SLN-T lymphocyte and control groups was 28 and 14 months, respectively. Our study showed that adjuvant SLN-T lymphocyte immunotherapy is feasible and safe for postoperative CRC patients. Additionally, this therapy may improve the long-term survival of metastatic CRC. Further investigation of the clinical efficacy and anti-tumor immunity is warranted.